NIGHT PARTY PUCUAK RABUANG MOTIF INSPIRATION - Anggara, Egi; Yanuarmi, Dini; Irja (Runtas : Journal Of Arts And Culture, 2024)
The work entitled “The Creation of Evening Party Dresses Inspired by the Pucuak Rabuang Motif” was inspired by evening party dresses and the pucuak raburan motif. Clothing is generally an expression or personal expression that is not always the same for everyone, the clothing created is an A-line silhouette evening party dress. Motif is a pattern that is formed in such a way as to produce a variety of shapes. The motif which is the source of the idea in this work is the pucuak raburan motif seen from the perspective of a mirror above the water. Everything that is visible above the water will be seen in two and upside down. Likewise, the pucuak raburan motif which is applied to this work resembles an inverted triangle motif as seen from above the water. The materials used are Silungkang songket, bridal sateen, brocade and velvet, consisting of ready to wear, ready to wear deluxe and houte couture clothing levels. In the embodiment using semi boutique techniques and boutique techniques. The method of creation that is carried out starts from preparation, namely looking for books or references related to the idea of ​​creation that is made, conducting a field survey to find the source of the idea or theme and the formulation of the idea of ​​creation to get to know more about the form of the work produced